Establishment of humidity moisture equilibrium and storage studies of dehydrated candied mango (Mangifera indica Linn.) - Vitasa, Alicia C.
The main objective of the study was to define a moisture range for optimum stability of dehydrated candied mango by analysis of its moisture sorption isotherm which is a necessary prerequisite for estimating its shelf life. The sorption isotherm was determined using the weight equilibrium method. The critical moisture content was found to be 27.16% (dry basis). The computed maximum allowable water vapor transmission rate was 10.11 g/m^2-day at 90% RH gradient at 28° to 30°C. Three packaging materials were selected based on the computed WVTR values, namely: low density polyethylene (.0015 inch), high density polyethylene (.002 inch) and polypropylene (.002 inch) . The shelf life was determined using the half-value period method. The study showed that all the packaging materials could be used for packaging dehydrated candied mango since the shelf life values obtained were greater than the desired shelf life.